The influence of Branding and Packaging on choice an overview of the retail market - Qadir Sofi, Umer (American Journal of Economics and Business Management, 2019)
In marketing, product packaging is very significant. Unforgettable speech influences consumer’s perception and ensures that customers keep coming back. For years, companies have been investigating how color influences purchasing decisions. Yellow color causes joy or fantasy, s - the beauty and perfect sensitivity of women’s perfumes, cosmetics and lotions, black - strength and strength, and so on. The color that the company chooses for packaging influences the choice of the buyer and often influences whether consumers remember the product with love and whether consumers let it is bought again.